Local immunie response in experimental pyelonephritis in the rabbit. III. Lymphocyte responsivieness to O and K antigens of Escherichia coli. - Smith, J W (1976)
The response of circulating and infected kidney lymphocytes to the O (lipopolysaccharide) and K (polysaccharide) antigens of an Escherichia coli O6 K 13 H1 strain was determined. Both circulating and kidney lymphocytes showed significant incorporation of [3H-methyl]thymidine into DNA when incubated with the O antigen, whereas neither responded to the K antigen. The lipid moiety of the lipopolysaccharide was required for lymphocyte responsiveness. Upon sequential incubation of O antigen and fluoresceinated homologous antiserum, 24-30 per cent of kidney lymphocytes were shown to have surface receptors for O antigen, whereas none had surface receptors for K antigen. Although the K antigen is an important determinant of invasiveness of the upper urinary tract, it fails to elicit a cellular immune response or attach to lymphocytes from the infected kidney in experimental pyelonephritis.